La arquitectura flexible en el habitar temporal de territorios fronterizos, para personas extranjeras en estado de vulnerabilidad (2023)
The purpose of the project is to understand how from the solutions of habitability through flexibility and adaptation in architecture, and its related issues, can mitigate the lack and quality of habitat infrastructure for vulnerable migrant population, in order to generate equity around the way of living and to help their migratory transition in terms of their basic primary needs, this, focused on border territories with high poverty rates and inequality in Colombia.